ANALISIS SEKTOR BASIS DAN SUBSEKTOR BASIS PERTANIAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN KEEROM PROVINSI PAPUA - Usman Usman (University of Jember, 2015)
Agricultural development program in Indonesia is the part of economic development.Papua Province in the economic sector, the agriculture sector is the very important role in supporting economic growth in the region.This study aims to analyze the basic sector and basic sub-sector of agriculture, analyze the position sector and the agriculture sector in the future, and the determinants of changes in positions on regional economic growth based on the calculation of the GDP Keerom district and Papua province in 2008-2011.The study used secondary data over a period of four years. The analysis method used is Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Total Shift Share (TSS). The analysis LQ show that agriculture sector is thebasic sector in the economy Keerom.While the agriculture sector as the sub-sector basis (leading sector) is plantation, animal husbandry, and forestry.The combined method of LQ and DLQ, show that agriculture sector is still the sector basis in the future.The results of the analysis TSS is known that the deciding factor position change on plantations and fishing sub-sector is the location factor, while the determining factor position change on the livestock sector is the factor of of economic structure.Key words: Agriculture, Location Quotient, Dynamic Location Quotient, Total Shift Share